2010
DOI: 10.1021/ol100073y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of New Chiral β-Amino Acid Derivatives by Mannich-type Reactions of Chiral N-Sulfinyl Imidates with N-Tosyl Aldimines

Abstract: New chiral beta-(sulfonylamino)sulfinylimidates are synthesized in high overall yield and excellent diastereomeric excess via highly anti-selective Mannich-type reactions of chiral N-tert-butanesulfinyl imidates with N-tosyl aldimines. Deprotection of the beta-(sulfonylamino)sulfinylimidates gave access to enantiopure imidate hydrochlorides in high yields, as useful intermediates for an easy transformation to new chiral beta-sulfonylamino amides upon simple heating in chloroform. Hydrolysis of the imidate hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In conclusion, we have demonstrated that δ‐chloro‐β‐amino‐ N ‐sulfinyl imidates can be readily prepared by highly anti ‐selective Mannich‐type reactions of δ‐chloro‐ N ‐sulfinyl imidates across aromatic N ‐sulfonyl aldimines. The complete anti diastereoselectivity of this reaction to give δ‐chloro‐β‐amino‐ N ‐sulfinyl imidates is consistent with the stereochemical outcome observed for α‐methyl‐substituted imidates 15f. Subsequent cyclization and deprotection reactions led to the formation of various chiral 2,3‐disubstituted piperidines such as 3‐amino‐2‐arylpiperidines and 2‐arylpiperidine‐3‐carboxylic acid derivatives, which belong to a class of compounds with potent biological activity or are of interest as valuable building blocks.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In conclusion, we have demonstrated that δ‐chloro‐β‐amino‐ N ‐sulfinyl imidates can be readily prepared by highly anti ‐selective Mannich‐type reactions of δ‐chloro‐ N ‐sulfinyl imidates across aromatic N ‐sulfonyl aldimines. The complete anti diastereoselectivity of this reaction to give δ‐chloro‐β‐amino‐ N ‐sulfinyl imidates is consistent with the stereochemical outcome observed for α‐methyl‐substituted imidates 15f. Subsequent cyclization and deprotection reactions led to the formation of various chiral 2,3‐disubstituted piperidines such as 3‐amino‐2‐arylpiperidines and 2‐arylpiperidine‐3‐carboxylic acid derivatives, which belong to a class of compounds with potent biological activity or are of interest as valuable building blocks.…”
Section: Discussionsupporting
confidence: 80%
“…The observed 2,3‐ anti diastereoselectivity of the addition reaction of N ‐sulfinyl imidate 8 across N ‐sulfonyl aldimines 9 can be rationalized by using a model in which the reaction proceeds via transition states TS‐1 and TS‐2 (Figure 2) with poor facial selectivity. Upon deprotonation of imidate 8 ,14c,15f the E ‐enolate, with the chloropropyl group and the N ‐ tert ‐butylsulfinyl group on opposite sides of the C–C double bond, will be preferentially formed. The N ‐sulfonyl aldimines (i.e., 9 ) adopt an E configuration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, N-sulfonyl imines have been widely used in various transformations in organic synthesis for access at biologically active compounds (6). They are excellent substrates in nucleophilic additions (7), Aza Diels-Alder reaction (8), reductions (9), oxaziridine (10) synthesis, asymmetric synthesis of β-amino acids derivatives (11), and reactive alkenes in ene reactions (12). In addition, they are excellent precursors for the preparation of optically active 2-imidazolines (13).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, N-sulfonyl imines have been widely used in organic transformations. 2 Furthermore, they are excellent substrates in nucleophilic additions, 3 reductions, 4 aza Diels-Alder reactions, 5 alternative aziridine synthesis involving nucleophilic addition across N-sulfonyl aldimines, 6 asymmetric synthesis of b-amino acid derivatives, 7 and oxaziridine synthesis, 8 as well as ene reactions. 9 Several kinds of synthetic routes toward N-sulfonyl imines have been developed namely via the Lewis and protic acid catalyzed reactions of sulfonamides with aldehyde precursors, [10][11][12][13][14][15][16][17][18][19][20][21][22] rearrangement of oxime O-sulfinates, 23 tellurium mediated reaction of aldehydes with chloramine T by utilization of in situ generated N,N9-ditosyltellurodiimide, 24 application of N-sulfinyl sulfonamides instead of sulfonamides to generate sulfonyl imines in situ via a [2 + 2] cycloaddition and extrusion of sulfur dioxide, 25 generation of sulfonamidosulfones and basic elimination, 26,27 and catalyzed isomerization or rearrangement of N-sulfonyl aziridines.…”
mentioning
confidence: 99%